'I really want to work for me to feel good myself ': Health impacts of employment experiences for women from refugee backgrounds in Australia - Anna Ziersch; Emily Miller; Moira Walsh; Clemence Due; Peta Callaghan; Joanna Howe; Erin Green (Elsevier, 2023)
Work is an important social determinant of health. However, people from refugee backgrounds face various barriers to employment and women especially have significantly lower levels of employment. Many refugees also work in jobs with poor conditions. Given the higher risk of poor health for refugees more generally, the impact of employment experiences on health is an important area of investigation. Drawing on in-depth interviews with 42 refugee women, this paper explores health effects of job seeking and employment experiences. Interviews were analysed using inductive thematic analysis. Women reported difficulties securing work and most were unemployed, which had a negative effect on mental health. Once in work, employment was found to promote wellbeing through a sense of identity and contribution, as well as extending social networks. However, almost all employed participants were working in precarious employment conditions. In terms of mental health, participants reported negative effects from exploitation and discrimination. Exposure to toxic chemicals and poor working conditions were reported as particularly detrimental to physical health. Women were reluctant to complain about poor working conditions, citing a lack of awareness of procedures, fear of losing employment, and concerns about implications for immigration status. Overall, the study highlighted significant barriers to women securing work generally, particularly work that was health promoting. The paper concludes with a discussion of the implications for policy and practice.